Deep Learning and Love Curriculum Integration in Indonesian Education - Erlina, Gusti; Riadi, Haris; Sulwana, Siti; Sa'diah, Halimatu (Pedagogia : Jurnal Pendidikan, 2026)
The integration of Deep Learning and a Love-Based Curriculum offers a strategic pedagogical model that aligns cognitive rigor with affective and moral development in Indonesian education. By uniting conceptual depth, critical inquiry, empathy, and character formation, this integrative approach supports holistic learning suited to the demands of 21st-century education and national character-building objectives. However, its effective implementation requires systematic teacher capacity building, adaptive instructional design, and the development of valid affective assessment instruments. This study provides a theoretical contribution by articulating an integrative learning paradigm that bridges cognitive and humanistic education, while practically offering guidance for educators and policymakers seeking to strengthen meaningful and character-oriented learning in Indonesia. Highlights: Mindful, meaningful, and joyful pedagogies reinforce critical reasoning and contextual application. Compassion-centered educational design strengthens empathy, moral awareness, and classroom inclusivity. Combined framework supports balanced development of intellectual, emotional, and spiritual capacities Keywords: Deep Learning, Love-Based Curriculum, Affective, Empathetic, Character Dimensions of Learners.